Analysis Effective Political Factors on Encouraging Investors to Facilitate Performance Investment Encouraging Policy in Municipality - Joybar, Manoucher; Etebarian, Akbar; Daei-Karimzadeh, Saeed (International Review of Management and Marketing, 2017)
Municipalities must try to make constant incomes and development and economic splendor for themselves. One of the optimum policy in this direction is development and promotion the culture of investment with using the potential of public and private sectors in the direction of constant and durable incomes in order to manage the affaires. Without doubt with proving to be true this aim, municipalities can take big steps to manage their policies and desires for economic development and welfare of citizenships. This present research has been done with the use of descriptive and measurement method in south province of west Azerbaijan. Statistical and research community was consist of 100 people; investment experts and managers in the south province of west Azerbaijan. These people are chosen with the use of sampling census method, data was collected with the use of constant and admissible questionnaire and analyzed with the SPSS 22 software. The result of investigations showed that political dimension is effective in encouraging investment for facilitate encouragement investment in municipalities. Keywords: political factors, investment, municipality JEL Classifications: E22, H54